Onwards and Upwards : Supporting the Transition to Key Stage One. - Orlandi, Kathleen (Taylor & amp, 2011)
How can teachers ensure that the transition from the Early Years Foundation Stage to Key Stage One is a positive experience for children? What are the issues for children, parents and teachers and how should teachers respond to these? This book introduces the concept of transition and identifies the key problem areas for children and adults focusing on the differences in philosophy and practice between the EYFS and Key Stage One, whilst also giving emphasis to the opportunities that are provided by the transition process. It stresses the need for a balanced approach and the importance of sustai.